Antiplatelet therapy in patients with atrial fibrillation: a systematic review and meta-analysis of randomized trials. Issue 7 (17th June 2021) - Benz, Alexander P; Johansson, Isabelle; Dewilde, Willem J M; Lopes, Renato D; Mehran, Roxana; Sartori, Samantha; Sarafoff, Nikolaus; Yasuda, Satoshi; McIntyre, William F; Healey, Jeff S; Shoamanesh, Ashkan; Eikelboom, John W; et al.
Abstract: Aims : The aim of this study was to systematically assess the effects of antiplatelets on clinical outcomes in patients with atrial fibrillation (AF), treated and not-treated with oral anticoagulation. Methods and results : We searched MEDLINE, Embase, and CENTRAL from inception until September 2020. From 5446 citations, we selected randomized trials allocating patients with AF to antiplatelet therapy vs. control. We applied random-effects models for meta-analysis and assessed potential effect modification with background anticoagulation use. Eighteen trials including 21 518 participants met our prespecified eligibility criteria. In 10 studies without background anticoagulation, antiplatelets reduced all-cause stroke [486/6165 (events/patients) vs. 621/6061; risk ratio (RR) 0.77, 95% confidence interval (CI) 0.69–0.86, I 2 = 0%]. In eight studies with background anticoagulation, there was a signal for an increase in all-cause stroke with antiplatelets (97/4608 vs. 72/4684; RR 1.33, 95% CI 0.98–1.79, I 2 = 0%, P -value for interaction <0.001). A similar pattern emerged for ischaemic stroke. Irrespective of background anticoagulation use, antiplatelets increased major bleeding (509/10 402 vs. 328/10 496; RR 1.54, 95% CI 1.35–1.77, I 2 = 0%) and intracranial haemorrhage (107/10 221 vs. 65/10 232; RR 1.64, 95% CI 1.20–2.24, I 2 = 0%), and reduced myocardial infarction (201/9679 vs. 260/9751; RR 0.79, 95% CI 0.65–0.94, I 2 = 0%, all P -values for interaction ≥0.36). Antiplatelets did not affect mortality (1221/10 299 vs. 1211/10 287; RR 1.02, 95% CI 0.89–1.17, I 2 = 29%, P -value for interaction = 0.23). Conclusions : In patients with AF not receiving oral anticoagulation, antiplatelet therapy modestly reduced stroke. There was a corresponding signal for harm when used on top of anticoagulation. Irrespective of background anticoagulation use, antiplatelet therapy significantly increased bleeding, moderately reduced myocardial infarction, and did not affect mortality.